2019
DOI: 10.1182/bloodadvances.2019000291
|View full text |Cite
|
Sign up to set email alerts
|

Related and unrelated donor transplantation for β-thalassemia major: results of an international survey

Abstract: We studied 1110 patients with β-thalassemia major aged ≤25 years who received transplants with grafts from HLA-matched related (n = 677; 61%), HLA-mismatched related (n = 78; 7%), HLA-matched unrelated (n = 252; 23%), and HLA-mismatched unrelated (n = 103; 9%) donors between 2000 and 2016. Ninety percent of transplants were performed in the last decade. Eight-five percent of patients received ≥20 transfusions and 88% were inadequately chelated. All patients received myeloablative-conditioning regimen. Overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…The 5-year probabilities of overall survival (OS) after HLA-matched relative, HLA-mismatched relative, HLA-matched unrelated, and HLA-mismatched unrelated donor transplants were reported to be 89%,73%, 87%, and 83%, respectively. The 5-year probabilities of EFS after HLA-matched relative, HLA-mismatched relative, HLAmatched unrelated, and HLA-mismatched unrelated donor transplants were 86%, 70%, 82%, and 78%, respectively [23]. This report shows comparable event-free and OS after HLA-matched related and HLA-matched unrelated donor transplantation.…”
Section: Bone Marrow Transplantationmentioning
confidence: 51%
“…The 5-year probabilities of overall survival (OS) after HLA-matched relative, HLA-mismatched relative, HLA-matched unrelated, and HLA-mismatched unrelated donor transplants were reported to be 89%,73%, 87%, and 83%, respectively. The 5-year probabilities of EFS after HLA-matched relative, HLA-mismatched relative, HLAmatched unrelated, and HLA-mismatched unrelated donor transplants were 86%, 70%, 82%, and 78%, respectively [23]. This report shows comparable event-free and OS after HLA-matched related and HLA-matched unrelated donor transplantation.…”
Section: Bone Marrow Transplantationmentioning
confidence: 51%
“…They reported that the 5-year probabilities of OS after HLA-matched relative, HLA-mismatched relative, HLA-matched unrelated, and HLA-mismatched unrelated donor transplants were 89%, 73%,87% and 83%, respectively. The 5-year probabilities of EFS after HLA-matched relative, HLA-mismatched relative, HLA-matched unrelated, and HLA-mismatched unrelated donor transplants were 86%, 70% and 82%, 78%, respectively 10. This report is the first demonstrating comparable event-free and overall survival after HLA-matched related and HLA-matched unrelated donor transplantation.…”
Section: Bone Marrow Transplantation (Bmt)mentioning
confidence: 61%
“…Overall survival (OS) and disease‐free survival (DFS) were highest in children aged ≤ 6 years who received grafts from HLA‐matched siblings or HLA‐matched unrelated donors. Five‐year OS rates in patients aged ≤ 6 years, 7–15 years, and 16–25 years were 91%, 83%, and 55%, respectively, and corresponding DFS rates were 87%, 79%, and 55%, respectively 13 …”
Section: Treatmentmentioning
confidence: 99%